Public Order and Security Prevention through Police Sector’s Friday Sharing Program Based on Hindu Values and Local Culture - I Kadek Sepri Juliadnyana; I Nyoman Raka; Ni Luh Gede Hadriani (Research Horizon, 2026)
Maintaining public security and order requires culturally sensitive and community-based preventive approaches. This study aims to analyze strategies for preventing disturbances to public security and order through the Friday Sharing Program, which is based on Hindu religious values and local culture. This qualitative study collected data through observation, in-depth interviews, and documentation. The results show that the Friday Sharing Program serves as an effective communication medium between the police and the community in conveying aspirations, complaints, and social issues related to public security and order. The integration of Hindu religious values such as dharma, karma phala, and tat twam asi, along with the concept of Tri Hita Karana, strengthens the preventive approach through moral development and social awareness within the community. In addition, local cultural values emphasizing togetherness, cooperation, and respect for traditions function as effective mechanisms of social control. Thus, the Friday Sharing Program not only functions as a forum for dialogue but also as a value-based preventive strategy capable of enhancing collective awareness in maintaining public security and order. This program contributes to strengthening the relationship between the police and the community, as well as maintaining social harmony amid the dynamics of modern life.